IBM's Tiny Peripheral: Finland and the Tensions of Transnationality - Petri Paju; Thomas Haigh (United States, 2022)
IBM Finland, a small national subsidiary, was at once a Finnish business and an interface to much larger networks of technological innovation and knowledge sharing. We contextualize its development within a nested set of institutions and identities: IBM's Nordic operations, its European business, and its World Trade Corporation. Its development was profoundly shaped by Finland's unique geopolitical position during the Cold War. IBM's internal structures anticipated and paralleled those of the European Union, with mechanisms for international cooperation, for the creation of transnational identities, and for the resolution and regulation of disputes between national subsidiaries.